MEASUREMENT OF THE QUALITY OF STATE ADMINISTRATIVE JUDGE DECISIONS IN DISPUTE SETTLEMENT IN STATE ADMINISTRATIVE COURTS - Adhi Wirawan Mulyono; Jonny Simamora; Edra Satmaidi (Universitas Bengkulu, 2022)
The quality of the decisions handed down by judges can be seen from the ratio decidendi or legal arguments given by the judges themselves. Before the judge decides to answer the plaintiff's demands, the judge first makes the basics of legal considerations containing legal arguments or reasons to arrive at a decision finally. Article 109 paragraph (1) of Law Number 5 of 1986 concerning the State Administrative Court stipulates that one thing that must be included in a judge's decision is the legal reason that forms the basis of the decision. The method used in this research is the empirical legal research method. This study used primary data and secondary data. The data obtained were analyzed juridical qualitatively utilizing deductive-inductive thinking. The decision has carried out the breadth of proof, the burden of proof, and the assessment of evidence, and the judge has assessed all evidence based on Article 109 of Law Number 5 of 1986 and supported by two pieces of evidence based on Article 107 of Law Number 5 of 1986, the reasons for the judge's refusal and accept the arguments of the plaintiff and the defendant is because the legal remedies do not carry out the decision. The application of Article 107 of Law Number 5 of 1986 concerning the State Administrative Court was then implemented into Article 109 paragraph 1 point d of Law Number 5 of 1986 concerning the State Administrative Court must be carried out in the context of creating a quality State Administrative Court decision.